Interaksi Islam dengan Budaya Barasandi dan Aktivitas Sosial Keagamaan Orang Tolaki di Sulawesi Tenggara - Basrin Melamba (UIN Maulana Malik Ibrahim Malang, 2012)
This research aimed to describe the interaction between Islam and Tolaki tradition in South East Sulawesi. The interaction between Tolaki and Islam has two formulations, the first, Islam contaminated, changed and reformed local culture, Tolaki. This kind of formulation produced the reality of religious social life like barasandi (bersanji/aqiqah), a marriage procession (mowindahako), a celebration of circumcision (maggilo), a celebration such a praying for being saved from any problem of life, a celebration of Prophet of Muhammad birth (Maulud Nabi), religious activities, an art and literature like kinoho agama (religious poems), Taenango langgai saranani (the history of heroic in Islamic spreading or proselytization in Tolaki region), religious social life like how someone performed or pilgrimaged to Mecca (hadi kobaraka), and the dynamics of social organization life. The second, Islam was contaminated by several local traditions. This case produced the process of Islam localizing in the the dynamics of Tolaki religious social community. There had been an interaction form and acculturation between Islam and Tolaki culture in Southeast Sulawesi. Penelitian ini bertujuan untuk menjelaskan interaksi atau perjumpaan antara agama Islam dengan budaya Tolaki di Sulawesi Tenggara. Interaksi Islam dengan kebudayaan Tolaki menghasilkan dua pola, pertama, Islam memberikan warna, mengubah, mengolah, dan memperbaharui budaya lokal. Pola ini memunculkan realitas kehidupan sosial keagamaan dalam bidang budaya Barasandi (aqiqah), adat perkawinan (mowindahako), upacara sunatan (manggilo), doa selamatan (mobasa-basa), peringatan maulid (maulu nabi), aktivitas keagamaan, dalam bidang seni dan sastra seperti kinoho agama (pantun agama), dan Taenango langgai saranani (kisah kepahlawanan dalam penyebaran agama Islam di wilayah Tolaki), serta kehidupan sosial keagamaan misalnya orientasi haji (hadi kobaraka), dan dinamika kehidupan organisasi sosial. Kedua, Islam diwarnai oleh berbagai budaya lokal. Saluran ini memunculkan proses lokalisasi unsurunsur Islam dalam dinamika sosial keagamaan orang Tolaki. Telah terjadi bentuk interaksi, dan akulturasi antara Islam dan budaya Tolaki di Sulawesi Tenggara